Response of Tenebrio molitor (Coleoptera: Tenebrionidae) adults to potato: Implications for monitoring and sampling. (January 2015) - Baek, Sunghoon; Perez, Anne E.; Turcotte, Richard M.; White, Joseph B.; Adedipe, Folukemi; Park, Yong-Lak
Abstract: Many stored product insect pests are known to be attracted to a moisture source, and thus vegetables with high moisture content could be used as an efficient and economical sampling and monitoring tool. This study was conducted to test the potential of using fresh-cut potato as a lure to attract Tenebrio molitor (Coleoptera: Tenebrionidae) adults. Preference of T. molitor adults to potato was determined using choice and non-choice tests, and food search behavior and movement of T. molitor adults in response to fresh-cut potato were investigated with videography and spatial analysis. The results of this study showed that T. molitor adults were attracted consistently to moisture and fresh-cut potato in both choice and non-choice olfactory tests. Tenebrio molitor adults showed preference to potato over media (i.e., both dry and wet oats). In spatial movement study, T. molitor adults were spatially oriented toward potato, and aggregated and stayed on potato. The results of this study suggest that fresh-cut potato can be used to attract T. molitor adults as an economical and environment-friendly lure for sampling and monitoring. Highlights: We hypothesized that T. molitor would be attracted to fresh-cut potato. Behavioral responses of T. molitor adults to moisture and potato were investigated. Tenebrio molitor adults were attracted and spatially aggregated on fresh-cut potato. Fresh-cut potato could be used as a lure for sampling and monitoring T. molitor .